Judicial Oversight of Negative Administrative Decisions - Hassan, Mustafa Rasul; Saeed, Hawraman Mohammed (Journal of Legal and Political Studies, 2016)
The Study looking for the administrative judiciary for the Negative administrative decisions , the study relied on descriptive method for its part.the administration has the right to with draw negative administrative decision at any time. Individuals with damage resulting from negative administrative decision entitled to claim compensation for damage before the administrative judiciary according to the act no.14 year 2008 Consultation Council of the Kurdistan Region - Iraq
Keywords: administrative judiciary; Compensation; Consultation Council of the Kurdistan Region; Damage